(3Qi GdChGe heQYi GdShGe aj fcJ GdNhGU hGdYhGes - (3YHjO Gddg Hf CMeO Hf eMeO, CHh jMji, GdnqRnqLGdj GdbQWHj,J (B694 (3g` s
(3ChdgG (B:s
(3hHYO agPG GdcJGH SejJg LeYJ ajg ETGQGJ GdbOeGA hYHGQGJ GdYdeGA hYXGJ GdadGSaI GdMceGA hJhbjYGJ Gdedhc GdYXeGA s
(3BNQgG (B:s
(3Efc eQHhH bOjQ JSCd hGdOgQ ai ZadI dGjZad MJi jLjF jhe GdeDLd GfJgi cJGH Qi GdChGe s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B191s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B55 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs